Carbon Nanotube Fiber Pretreatments for Electrodeposition of Copper - Pyry-Mikko Hannula; Minttu Junnila; Dawid Janas; Jari Aromaa; Olof Forsén; Mari Lundström (Advances in Materials Science and Engineering)
There is increasing interest towards developing carbon nanotube-copper (CNT-Cu) composites due to potentially improved properties. Carbon nanotube macroscopic materials typically exhibit high resistivity, low electrochemical reactivity, and the presence of impurities, which impede its use as a substrate for electrochemical deposition of metals. In this research, different CNT fiber pretreatment methods, such as heat treatment, immersion in Watts bath, anodization, and exposure to boric acid (H3BO3), were investigated to improve the electrochemical response for copper deposition. It was shown that these treatments affect the surface activity of CNTs, including electrical resistivity, polarization resistance, and active surface area, which influence the electrodeposition process of copper. Properties of CNT structures and CNT-Cu composites were researched by electrochemical impedance spectroscopy (EIS), galvanostatic copper deposition, scanning electron microscope (SEM), and four-point electrical resistance measurements. Heat treatment, Watts bath, anodization, and boric acid treatments were shown to be effective for modifying the CNT surface reactivity for subsequent electrochemical deposition of copper.